Hip and knee arthroplasties in military personnel improve unilateral spinal anesthesia combined with unilateral epidural analgesia. - Rakhmankulov E.J. Ph.D.,; Mirrakhimova S.Sh. Ph.D; Professor Avakov V.E.; Chakganov O'.A. (Zien Journals, 2025)
Surgery is often performed on the feet to produce the necessary sensory blockade with minimal effects on the sympathetic nervous system . application of local anesthesia (SA, EA). preferred [133; 105-115 p]. The purpose of unilateral US is to limit the spread of somatic and sympathetic blockade [ 106; 2379-2402- b ] it primarily reduces hemodynamic complications It provides a number of clinical advantages and [53; 298-311-p] our study patients with low cardiac output It is useful for elderly patients with hypodynamic circulatory conditions
Keywords: Charles number comorbidity index; it is unilateral spinal anesthesia; epidural anesthesia